The Effect Of Processed Mackerel On Increasing The Weight Of Toddlers In Bogor And Cianjur Districts - Pratiwi, Regina; Hanifa, Fanni; Hindayani, Hindayani; Oktianingsih, Neti; Santika, Asri; Supriyatin, Supriyatin; Notiasary, Marina (Jurnal Maternitas Kebidanan, 2025)
According to WHO, malnutrition problems can be grouped into wasting, stunting, underweight, and micronutrient deficiencies. Wasting is a condition when a person's weight per height is low. WHO data in 2020 showed that the prevalence of toddlers experiencing wasting globally was 45.4 million toddlers (8%). Indonesia is still the second country with the highest wasting cases in the world with a prevalence of wasting toddlers of 7.7% (UN, 2022, SSGI 2022). The government has tried to overcome the problem of malnutrition in toddlers with a program to provide additional food made from local ingredients (DitGiziKIA, 2022). Some of the local food sources that are high in protein are mackerel and snakehead fish. The purpose of this study was to determine the effect of processed mackerel on increasing the weight of toddlers in Bogor and Cianjur Regencies in 2025. who was given intervention? The results of this study are that providing additional food-processed mackerel is proven to increase the weight of toddlers by an average of 275 grams/week.